Program Kelas Inspirasi sebagai Upaya untuk Meningkatkan Motivasi Siswa SMKN 2 Tapung Hilir untuk Melanjutkan Pendidikan ke Perguruan Tinggi - Dina Syaflita; Diani Sukmadewi; Fanny Nurmaulida; Fatinatus Zahro; Hafshoh; Muthia Raudha; Ranty Andika Abinaya Zameza; Ilham Akbar Siregar; Lukas Probondany Waris Wasiso; Roihan Alfaini; Trisput DT Zebua (INTEGRATIF: Jurnal Pengabdian Kepada Masyarakat, 2024)
The existence of negative stigma and the lack of information causes the low interest of students to continue their studies to higher education. The “Inspiration Class” program aims to provide information related to the world of lectures to break negative stigma and increase students' interest in further studies. This activity was carried out at the Vocational High School 2 Tapung Hilir. This activity was held in July 2022 which was attended by class XI majoring in Motorcycle Business Engineering (TBSM) or Plantation Agribusiness. The resource persons in this activity were the dedication team from the University of Riau which consisted of lecturers and students in field practice. The steps for implementing this activity include the planning, implementation, and evaluation stages. Overall the level of achievement of this activity is very satisfactory where this results was evaluated through responses, enthusiasm and questions from activity participants about the materials that have been delivered, both materials related to negative stigmas about lectures and or materials related to scholarships.